Tatalaksana Proses Asuhan Gizi Terstandar pada Pasien Diabetes Melitus Tipe 2 dengan Sepsis Pasca Operasi Gangren - Astuti, Nur Fitri Widya; Maharani , Alya Orsa; Wahyuni, Endang Sri (Student Journal Nutrition (SJ Nutrition), 2023)
Background : Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. One of the complications that can be caused by DM is gangrene, which is an infection of the feet due to a reduction in oxygen flow to the organs. This causes tissue death and if severe can cause amputation in people with DM. The management of managing DM is not only by administering medication, but also by diet therapy. This is aimed at maintaining the patient's nutritional status. It is necessary to carry out a Standardized Nutritional Care Process (NCP) to optimize nutritional services for DM patients Objective : To determine the effect of the Standardized Nutrition Care Process (NCP) on type 2 DM patients with sepsis after gangrene surgery Research Methods : The method used in this research was qualitative descriptive research with a case study approach. The subject in this case study was a 52 year old female patient who was treated at RSUD dr. Soebandi Jember with a medical diagnosis of type 2 DM with sepsis after gangrene surgery. Patients was given a standardized nutritional care process during hospitalization. The research time was 3-7 November 2022. Research analysis uses using descriptive analysis. Research Result : The results of NCP showed that the patient had underweight nutritional status. During monitoring, the evaluation showed that the patient's blood biochemical levels during the nutritional care process had not shown improvement because they were still below normal values. Furthermore, the patient's physical and clinical condition improved even though his appetite was still low. Then the results of the consumption survey with 24-hour food recall show that the patient's food intake is still <80%, still in the severe deficit category during the process of providing nutritional care. Conclusion : NCP provides to patients has not shown significant improvement due to post-surgery. There is a need to modify the food menu and motivate patients to increase the patient's appetite and food intake so that the patient's nutritional status can be improved.